β2 Integrin Regulation of Neutrophil Functional Plasticity and Fate in the Resolution of Inflammation - Sekheri, Meriem; Othman, Amira; Filep, János G. (Frontiers in Immunology, 2021)
Neutrophils act as the first line of cellular defense against invading pathogens or tissue injury. Their rapid recruitment into inflamed tissues is critical for the elimination of invading microorganisms and tissue repair, but is also capable of inflicting damage to neighboring tissues. The β2 integrins and Mac-1 (CD11b/CD18, αMβ2 or complement receptor 3) in particular, are best known for mediating neutrophil adhesion and transmigration across the endothelium and phagocytosis of microbes. However, Mac-1 has a broad ligand recognition property that contributes to the functional versatility of the neutrophil population far beyond their antimicrobial function. Accumulating evidence over the past decade has demonstrated roles for Mac-1ligands in regulating reverse neutrophil transmigration, lifespan, phagocytosis-induced cell death, release of neutrophil extracellular traps and efferocytosis, hence extending the traditional β2 integrin repertoire in shaping innate and adaptive immune responses. Understanding the functions of β2 integrins may partly explain neutrophil heterogeneity and may be instrumental to develop novel therapies specifically targeting Mac-1-mediated pro-resolution actions without compromising immunity. Thus, this review details novel insights on outside-in signaling through β2 integrins and neutrophil functional heterogeneity pertinent to the resolution of inflammation.